Evaluasi Sistem Pelayanan Sistem Administrasi Manunggal Satu Atap (SAMSAT) Corner Dalam Meningkatkan Kepuasan Wajib Pajak - Wardana, Gede Angga; Erviantono, Tedi; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2015)
Abstract The implementation of SAMSAT (One stop Administrative System) Corner program makes taxpayers greatly assisted. This is because the service in the SAMSAT Corner is provided until night time. However, behind the good service system in SAMSAT Corner, of course, there are still some shortcomings starting from a lack of rules or legal grounds about SAMSAT Corner to services which still give unfair selection treatment of customers. The purpose of this study was to know forms of service of SAMSAT Corner and to know ideal models of tax payment services based on the input of the community. This study used a qualitative descriptive method to obtain data, the writer made observations by watching directly the phenomena happening in the field and conducted in-depth interviews with resource persons associated with SAMSAT Corner service system and taxpayers as service users of SAMSAT Corner. The findings showed that were several innovations suggested by the community, they are, SAMSAT Banking, SAMSAT Go To Village Program and SAMSAT Drive Thru. Beside that there are very important obstacles from this study, there are still brokers as main comprtitors for the innovation of SAMSAT. Keywords: Obstacles of SAMSAT, Community Inovation, Public Service Quality